2020
DOI: 10.1002/jbmr.4807
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bone Volume by Ixazomib in Multiple Myeloma: 3-Month Results from an Open Label Phase 2 Study

Abstract: Multiple myeloma (MM) is an incurable bone marrow cancer characterized by the development of osteolytic lesions due to the myeloma-induced increase in osteoclastogenesis and decrease in osteoblastic activity. The standard treatment of MM often involves proteasome inhibitors (PIs), which can also have a beneficial off-target bone anabolic effect. However, long-term treatment with PIs is unadvised due to their high side-effect burden and inconvenient route of administration. Ixazomib is a new-generation, oral PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…The effect of ixazomib on myeloma bone disease is currently being investigated in a clinical trial on patients with MM in remission (clinaltrials.gov NCT04028115, accessed on 1 November 2023). Recently published preliminary results from this trial [136] revealed a drug-mediated increase in trabecular bone volume mediated by decreased osteoclast activity and longer bone formation events in bone biopsies taken after just 3 months of treatment [136]. Daratumumab, a CD38 antibody that is extensively used to treat MM, has also demonstrated positive effects on bone formation.…”
Section: Targeting the Microenviromentmentioning
confidence: 97%
“…The effect of ixazomib on myeloma bone disease is currently being investigated in a clinical trial on patients with MM in remission (clinaltrials.gov NCT04028115, accessed on 1 November 2023). Recently published preliminary results from this trial [136] revealed a drug-mediated increase in trabecular bone volume mediated by decreased osteoclast activity and longer bone formation events in bone biopsies taken after just 3 months of treatment [136]. Daratumumab, a CD38 antibody that is extensively used to treat MM, has also demonstrated positive effects on bone formation.…”
Section: Targeting the Microenviromentmentioning
confidence: 97%
“…Third, it can be hypothesized that continuous ixazomib treatment has influenced the bone marrow microenvironment by inhibiting osteoclasts while maintaining/stimulating the proliferation of osteoblasts. [8][9][10] Notably, osteoblasts are known to trigger apoptosis and cell cycle arrest in plasma cells. 11 Whether the indirect effects of ixazomib, through its impact on osteoblasts, contribute to the improvement in OS remains to be substantiated; and the fact why such an impact would be less in subsequent lines of therapy, as PIs were more often used in patients not having received ixazomib maintenance in first line.…”
mentioning
confidence: 99%